One session treatment (OST) is equivalent to multi‐session cognitive behavioral therapy (CBT) in children with specific phobias (ASPECT): results from a national non‐inferiority randomized controlled trial. (1st August 2022) - Wright, Barry; Tindall, Lucy; Scott, Alexander J.; Lee, Ellen; Cooper, Cindy; Biggs, Katie; Bee, Penny; Wang, Han‐I; Gega, Lina; Hayward, Emily; Solaiman, Kiera; Teare, M. Dawn; et al.
Abstract : Background: 5%–10% children and young people (CYP) experience specific phobias that impact daily functioning. Cognitive Behaviour Therapy (CBT) is recommended but has limitations. One Session Treatment (OST), a briefer alternative incorporating CBT principles, has demonstrated efficacy. The Alleviating Specific Phobias Experienced by Children Trial (ASPECT) investigated the non‐inferiority of OST compared to multi‐session CBT for treating specific phobias in CYP. Methods: ASPECT was a pragmatic, multi‐center, non‐inferiority randomized controlled trial in 26 CAMHS sites, three voluntary agency services, and one university‐based CYP well‐being service. CYP aged 7–16 years with specific phobia were randomized to receive OST or CBT. Clinical non‐inferiority and a nested cost‐effectiveness evaluation was assessed 6‐months post‐randomization using the Behavioural Avoidance Task (BAT). Secondary outcome measures included the Anxiety Disorder Interview Schedule, Child Anxiety Impact Scale, Revised Children's Anxiety Depression Scale, goal‐based outcome measure, and EQ‐5DY and CHU‐9D, collected blind at baseline and six‐months. Results: 268 CYPs were randomized to OST ( n  = 134) or CBT ( n  = 134). Mean BAT scores at 6 months were similar across groups in both intention‐to‐treat (ITT) and per‐protocol (PP) populations (CBT: 7.1 (ITT, n  = 76), 7.4 (PP, n  = 57), OST: 7.4 (ITT, n  = 73), 7.6 (PP, n  = 56), on the standardized scale‐adjusted mean difference for CBT compared to OST ‐0.123, 95% CI −0.449 to 0.202 (ITT), mean difference −0.204, 95% CI −0.579 to 0.171 (PP)). These findings were wholly below the standardized non‐inferiority limit of 0.4, suggesting that OST is non‐inferior to CBT. No between‐group differences were found on secondary outcomes. OST marginally decreased mean service use costs and maintained similar mean Quality Adjusted Life Years compared to CBT. Conclusions: One Session Treatment has similar clinical effectiveness to CBT for specific phobias in CYP and may be a cost‐saving alternative.